Development Approach for Tourism Following the Film and TV Series Trails in Thailand - Ngamsilstian, Atithep (Dusit Thani College Journal, 2020)
The growth of the number of tourists entering Thailand has continued to increase. By tourist groups, in addition to having purchasing power, there is also a trend for new places and cultures which tourism following the film and TV series trails in Thailand is another form of travel that is getting a lot of attention. This article aims to 1) study situations, models, needs and trends of tourism following the film and TV series trails in Thailand 2) propose development approach for tourism following the film and TV series trails in Thailand. The analysis results showed that Thailand has the potential to be a target for filming and TV series locations because of its wide variety of beautiful locations. Government agencies are integrating marketing ingredients to stimulate the tourism trail. As for the guidelines for tourism development following the film and TV series trails in Thailand, it was found that all parties of the public and private sectors should seriously integrate the development of the film and TV series industry. The public sector should fully support private sector funding and increase the publicity of beautiful Thai places through movies and TV series in order to promote tourist attractions to be well known both domestically and abroad, including facilitating and increasing incentives for the filming team to be superior to the competition. The private sector should develop script writing and filming in Thailand to be more efficient.